Self‐reported sleep disturbance is associated with Alzheimer's disease risk in men. Issue 9 (27th October 2014) - Benedict, Christian; Byberg, Liisa; Cedernaes, Jonathan; Hogenkamp, Pleunie S.; Giedratis, Vilmantas; Kilander, Lena; Lind, Lars; Lannfelt, Lars; Schiöth, Helgi B.
Abstract : Objective: To study the association between self‐reported sleep disturbances and dementia risk. Methods: Self‐reported sleep disturbances and established risk factors for dementia were measured in men at ages 50 (n = 1574) and 70 (n = 1029) years. Dementia incidence was determined by reviewing their patient history between ages 50 and 90 years. In addition, plasma levels of β‐amyloid (Aβ) peptides 1–40 and 1–42 were measured at ages 70, 77, and 82 years. Results: Cox regression demonstrated that men with self‐reported sleep disturbances had a higher risk of developing dementia (+33%) and Alzheimer's disease (AD, +51%) than men without self‐reported sleep disturbances (both P  < .05). Binary logistic regression showed the increased risk for both dementia (+114%) and AD (+192%) were highest when sleep disturbance was reported at age 70 years (both P  < .001). No group differences were found in Aβ levels. Conclusion: Improving sleep quality may help reduce the neurodegenerative risk in older men.